MicroRNA Profiling of Differentiated, Poorly Differentiated and Anaplastic Thyroid Carcinoma, a Comparative Approach - P Menon Madhu; Schattgen Stefan; Tadiri Sarah; Khan Ashraf (Journal of Cancer Genetics And Biomarkers, 2015)
Thyroid carcinomas encompass a wide spectrum ranging from differentiated thyroid carcinoma (DTC) to poorly differentiated (PDC) and anaplastic thyroid carcinoma (ATC). DTC of both follicular (FTC) and papillary (PTC) types can progress to PDC and AC. The aim of our study was to evaluate if there is differential microRNA (miRNA) expression in various tumor subtypes during this progression. The miRNA profile of differentiated carcinomas (Follicular and Papillary) and ATC were compared with that of PDCs either by itself or in a background of differentiated carcinomas and anaplastic carcinomas. Unsupervised hierarchical clustering analysis revealed that FTC and PDC tend to cluster together in the absence of ATC. Interestingly, in cases with presence of all components i.e. FTC, PDC and ATC, the miRNA profile of poorly differentiated component clusters with that of the Anaplastic carcinoma component. miR-494 and miR-125a-5p were found to be differentially regulated in tumors with an anaplastic component and even the well-differentiated component (FTC) of these tumors were found to be aligned with the anaplastic profile. In addition, we also discovered some differentially regulated miRNAs in follicular variant of papillary thyroid carcinoma as compared to follicular thyroid carcinoma (miR-486-5p and miR-31).
Keywords: Cancer